2013
DOI: 10.5144/0256-4947.2013.290
|View full text |Cite
|
Sign up to set email alerts
|

The distribution ofcagAanddupAgenes inHelicobacter pyloristrains in Kurdistan region, northern Iraq

Abstract: BACKGROUND AND OBJECTIVESHelicobacter pylori is a Gram negative bacteria that causes peptic ulceration and gastric adenocarcinoma. H pylori virulence factors, such as cagA and dupA, are important to study in populations as they contribute to disease risk. This study aimed to look at the distribution of the cagA and dupA genes in H pylori strains isolated from patients suffering from gastroduodenal diseases in Kurdistan region, Iraq.DESIGN AND SETTINGSA cross-sectional study conducted between June 2011 and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
4
5
0
1
Order By: Relevance
“…We looked within our populations for the associations between virulence factors and PUD. In agreement with previous reports from Iraq [19–21] , a significant association between cagA status and PUD was observed. Also, research from a neighbouring country, Turkey, has shown results similar to those from Iraq [3] .…”
Section: Discussionsupporting
confidence: 93%
“…We looked within our populations for the associations between virulence factors and PUD. In agreement with previous reports from Iraq [19–21] , a significant association between cagA status and PUD was observed. Also, research from a neighbouring country, Turkey, has shown results similar to those from Iraq [3] .…”
Section: Discussionsupporting
confidence: 93%
“…In line with our study, some authors were unable to regard dup A as a predictor of duodenal ulceration in Belgium, South Africa, China and North America [55]. We recorded 53.4% dup A positive isolates in our study, while the lower prevalence of dup A (18.8%) was reported in Northern Iraq [26] and as well as 39% in Iran [56].…”
Section: Discussionsupporting
confidence: 81%
“…One study from Kurdistan region of Northern Iraq reported that cagA gene was significantly associated with peptic ulcer disease rather than dupA , which contradict the result of Hussein et al[ 29 ] (2008). This might be due to the differences in sample size and also in the geographical location of Iraq[ 34 ]. In the Shiraz area of Iran, a significant relationship was found between strains with dupA , CagA motif (ABC types) and DU disease, which supports the previous finding in this region[ 35 ].…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%